Lower-limb joint mechanics during maximum acceleration sprinting - Schache, A. G.; Lai, A. K. M.; Brown, N. A. T.; Crossley, K. M.; Pandy, M. G. (The Journal of Experimental Biology, 2019)
We explored how humans adjust the stance phase mechanical function of their major lower-limb joints (hip, knee, ankle) during maximum acceleration sprinting. Experimental data [motion capture and ground reaction force (GRF)] were recorded from eight participants as they performed overground sprinting trials. Six alternative starting locations were used to obtain a dataset that incorporated the majority of the acceleration phase. Experimental data were combined with an inverse-dynamics-based analysis to calculate lower-limb joint mechanical variables. As forward acceleration magnitude decreased, the vertical GRF impulse remained nearly unchanged whereas the net horizontal GRF impulse became smaller as a result of less propulsion and more braking. Mechanical function was adjusted at all three joints, although more dramatic changes were observed at the hip and ankle. The impulse from the ankle plantar-flexor moment was almost always larger than those from the hip and knee extensor moments. Forward acceleration magnitude was linearly related to the impulses from the hip extensor moment (R2=0.45) and the ankle plantar-flexor moment (R2=0.47). Forward acceleration magnitude was also linearly related to the net work done at all three joints, with the ankle displaying the strongest relationship (R2=0.64). The ankle produced the largest amount of positive work (1.55±0.17 J kg-1) of all the joints, and provided a significantly greater proportion of the summed amount of lower-limb positive work as running speed increased and forward acceleration magnitude decreased. We conclude that the hip and especially the ankle represent key sources of positive work during the stance phase of maximum acceleration sprinting.